Innovative Comprehensive Experiments to Study the Morphological Changes of Apoptotic Cells for Undergraduate Education. Issue 3 (27th February 2019) - Song, Qing; Liu, Tingting; Yang, Hua; Bai, Yun
Abstract: This innovative comprehensive experiment is a compulsory course for third‐year undergraduate students in the eight‐year training program leading to a Doctor of Medicine degree or Doctor of Philosophy degree at Peking University Health Science Center (PKUHSC). There is a critical educational need to prepare these students for the increasing accessibility of research experience. This experimental curriculum of medical cell biology was developed to fulfill such a requirement, which consists of three experiments, including the MTT (3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide tetrazolium) assay and the immunofluorescence and comet assays to observe antitumor drug‐induced cell apoptosis. This experiment‐based teaching system provides the participating students an opportunity to enhance their understanding of important biological research techniques and the instrumentation involved and to foster a better understanding of the research process within the classroom. Upon completion of the course, students' feedback showed that the curriculum increased their confidence in performing molecular techniques, and they reported positively on doing a research project in class. This course helped students improve their understanding of theoretical knowledge and actual research processes and contributed to their foundation for future research. © 2019 International Union of Biochemistry and Molecular Biology, 47(3):348–354, 2019.